Feasibility Studi Business Marketing Development and Inovation in CV Bonee Enggenering Bandung Indonesia - Kadir, Andi Abdul; Supriadi, Supriadi (Lembaga Riset Mutiara Akbar (LARISMA), 2022)
The world of business and industry has great potential and can be a major contributor to Indonesia's economic development. This research is the initial stage that provides the foundation for subsequent research with a focus on Innovation Strategy, Product Development and Market Orientation. The goal is to describe the mapping of potential markets with product innovation. product innovation developed to meet the market by determining the road map and research design. The theoretical basis for success in introducing new products to the market depends on market-oriented strategic management. Market orientation is defined as the industry's method of market intelligence relating to current and future customer needs, then spreading the adopted market intelligence results throughout the value chain and the industry's ability to respond. Methodology with literature study was used in this research and analysis. The determination of the Five Competitive Forces (FCF) variable is also measured through key Performance Indicators. The scoring results are then mapped to see the determining factors. The SWOT model is applied to conclude the strengths and opportunities, weaknesses and threats faced by CV Bone engineering to determine competitive strengths and innovation needs.